Characterization of Salinity Tolerance of Transgenic Rice Lines Harboring HsCBL8 of Wild Barley (Hordeum spontanum) Line from Qinghai-Tibet Plateau - Guo, Wanli; Chen, Tianlong; Hussain, Nazim; Zhang, Guoping; Jiang, Lixi (Frontiers in Plant Science, 2016)
Rice is more sensitive to salinity, particularly at its early vegetative and later productive stages. Wild plants growing in harsh environments such as wild barley from Qinghai-Tibet Plateau adapt to the adverse environment with allelic variations at the loci responsible for stressful environment, which could be used for rice genetic improvement. In this study, we overexpressed HsCBL8 encoding a calcium-sensor calcineurin B-like (CBL) protein in rice. The gene was isolated from XZ166, a wild-barley (Hordeum spontanum) line originated from Qinghai-Tibet Plateau. We found that XZ166 responded to high NaCl concentration (200 mM) with more HsCBL8 transcripts than CM72, a cultivated barley line known for salinity tolerance. XZ166 is significantly different from CM72 with nucleotide sequences at HsCBL8. The overexpression of HsCBL8 in rice resulted in significant improvement of water protection in vivo and plasma membrane, more proline accumulation, and a reduction of overall Na+ uptake but little change in K+ concentration in the plant tissues. Notably, HsCBL8 did not act on some genes downstream of the rice CBL family genes, suggesting an interesting interaction between HsCBL8 and unknown factors to be further investigated.